Kontribusi Variabel Makro Ekonomi Terhadap Harga Saham Kelompok Jakarta Islamic Index 70 di Indonesia - Alindra Yanuardi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze how inflation and interest rates affect stock prices included in the Jakarta Islamic Index 70 (JII70) during the period 2019 to 2022. By applying saturated sampling techniques, the researcher obtained a total of 70 companies that are members of the JII70. To analyze the data obtained, the method used is multiple linear regression. The results of the analysis show that inflation does not have a significant impact on stock prices from the JII70 group. On the contrary, interest rates are proven to have a significant effect on stock prices in the period studied. Through multiple linear regression tests, it was found that the unstandardized coefficients for the inflation variable were the lowest when compared to the interest rate variable. However, inflation shows a negative correlation with stock prices in the JII70 group. On the other hand, interest rates show a positive correlation, which means that an increase in interest rates will be followed by an increase in stock prices in the JII70 group. These findings indicate that the interest rate factor plays an important role in stock price movements, while inflation does not contribute significantly in this context. This can provide insight for investors and stakeholders in making more appropriate investment decisions based on existing economic dynamics.